PENGARUH KOMPETENSI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR BALAI BESAR KONSERVASI SUMBERDAYA ALAM (KSDA) SULAWESI SELATAN DI MAKASSAR - Maswiati Maswiati (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The purpose of this study is whether the Competence, Motivation and Work Environment has a positive and significant influence and which variables are the dominant influence on Performance of The Great Hall for Conservation of Natural Resources in South of Sulawesi in Makassar. The research method used secondary data and primary data up to 59 samples, Data collection methods used were observation, documentation, interviews, and questionnaires.. The analysis model used is descriptive statistics and multiple regression analysis. The results explained 1) Competence has an effect but didn’t significant on PerformanceThe Great Hall for Conservation of Natural Resources in South of Sulawesi in Makassar. 2) Motivation has a positive and significant to Performance The Great Hall for Conservation of Natural Resources in South of Sulawesi in Makassar. 3) Work Environment has an effect but didn’t significant to Performance The Great Hall for Conservation of Natural Resources in South of Sulawesi in Makassar.4) Motivation has a dominant influence on Performance The Great Hall for Conservation of Natural Resources in South of Sulawesi in Makassar.